2016
DOI: 10.1016/j.sbi.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

SPLINTS: small-molecule protein ligand interface stabilizers

Abstract: Regulatory protein-protein interactions are ubiquitous in biology, and small molecule protein-protein interaction inhibitors are an important focus in drug discovery. Remarkably little attention has been given to the opposite strategy – stabilization of protein-protein interactions, despite the fact that several well-known therapeutics act through this mechanism. From a structural perspective, we consider representative examples of small molecules that induce or stabilize the association of protein domains to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 56 publications
1
32
0
Order By: Relevance
“…Molecular glues refer to small-molecule PPI stabilizers that bind a protein and modify its molecular surface, thus enabling it to recruit a new protein ( Figure 1 ) [ 14 ]. Several examples of molecular glues can be found in nature, including some macrocyclic agents initially thought to act via conventional inhibition.…”
Section: Molecular Glues and The Modulation Of Protein–protein Interamentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular glues refer to small-molecule PPI stabilizers that bind a protein and modify its molecular surface, thus enabling it to recruit a new protein ( Figure 1 ) [ 14 ]. Several examples of molecular glues can be found in nature, including some macrocyclic agents initially thought to act via conventional inhibition.…”
Section: Molecular Glues and The Modulation Of Protein–protein Interamentioning
confidence: 99%
“…The resulting ternary complex of FRB:rapamycin:FKBP12 shows de novo interactions between the FRB domain and FKPB12 in addition to interactions between rapamycin and both proteins [ 19 , 20 ]. The precise mechanism of action is still unknown, but it is suggested that FKB12 may impede access to the mTOR catalytic site [ 14 ].…”
Section: Molecular Glues and The Modulation Of Protein–protein Interamentioning
confidence: 99%
“…Targeted protein degradation refers to small molecule induced ubiquitination and degradation of disease targets, in which a small molecule simultaneously recruits both a ubiquitin E3 ligase and the target protein to be ubiquitinated (Supplementry Fig. 1a); therefore, representing a functional application of chemically induced protein dimerization 8,11 . Clinical proof of concept for targeted protein degradation is provided by the recent discovery that the potent anti-cancer drugs thalidomide, lenalidomide and pomalidomide (collectively known as IMiDs for immuno-modulatory drugs) exert their therapeutic effects through induced degradation of key efficacy targets, such as IKZF1, IKZF3 1214 , ZFP91 15 , or casein kinase 1 alpha (Ck1α) 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…[2] Thes ignificant roles of CRLs in several biological processes and human diseasesh as rapidly emerged, in particulari nc ancer, where the genes encoding for E3 ligase subunits and their native substrates are often found as oncogenes or tumors uppressors. [3] Currently, much focus is directed towardt argeting E3 CRLs with small molecules, such as inhibitors, to block the ligase activity; [4] molecular glues, to redirect E3 CRL activity toward neo-substrates; [5] and bivalent PROTACs, to induce targeted protein degradation. [6,7] These chemical modalities motivate the growing interest in studying this class of enzymes.W hile E3 inhibitors, molecular glues and PROTACs have been widely reported, to our knowledge there are only af ew examples of small moleculesd eveloped to disrupti nter-subunit assembly within CRLs.…”
mentioning
confidence: 99%